Sustainability Activities Disclosure and The Financial Performance: Study of Sharia Compliance Company in Indonesia - Puspitasari, Novi; Fauziyah, Hanif; Endhiarto, Tatok; Azis, Norazlin binti Ab (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The increasing issues of natural damage remind people of the importance of managing limited natural resources so that companies can use them efficiently, especially in meeting their operating needs. This study was conducted on this phenomenon to determine how sustainability reports affect the company's performance. The population used in this study was 244 Sharia Securities companies during 2018-2022. This study got 27 research samples using a purposive sampling method. This research conducted multiple linear regression analysis methods. Results showed that only the environmental dimension of sustainability disclosure positively affects significantly on company performance. The findings suggest a positive correlation between comprehensive sustainability disclosures and improved financial performance, highlighting the potential for Islamic economic principles to support sustainable development goals. Then this study contributes to the growing body of literature on Islamic finance and corporate responsibility, offering practical implications for policymakers, investors, and Sharia-compliant firms aiming to enhance transparency, accountability, and long-term value creation in a islamic-based economic framework.